Peran ayah dalam pendidikan anak masa pandemi pada keluarga wanita karir (Perspektif gender, pendidikan dan psikologi) - Dian Risky Amalia; M. Agus Mushodiq; Masrurotul Mahmudah; Isnaini Nur Azizah; Rizky Hidayatullah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2022)
From the point of view of economic needs, many women today prefer to be career women as well as housewives. It has become an entrenched demand, and even more so during the Covid-19 pandemic, women are required to be multitalented. Meanwhile, in some families, patriarchal culture is still an obstacle to the limited movement of women. This study uses a qualitative analysis with ethnographic methods and an empirical sociological approach that uses the sociological theory of Patirim Sorokin, which focuses on three things, namely ideational culture, sensory culture, and mixed culture. This study concludes that the ideational culture or world view of patriarchal culture has been rooted in the archipelago since ancient times, where the main role of women is at home while men are more likely to work to provide for the family. However, in sensory culture, there are many couples who help each other or create gender equality for the realization of a harmonious and dynamic family. Mixed culture exists in many husbands and wives who both work and cannot share the time, energy and thoughts to pay attention to their children.